Medications for sleep schedule adjustments in athletes - Baird, M. B.; Asif, I. M. (Sports Health: A Multidisciplinary Approach, 2018)
Context: Sleep schedule adjustments are common requirements of modern-day athletes. Many nonpharmacologic and pharmacologic strategies exist to facilitate circadian rhythm shifts to maximize alertness and performance during competition. This review summarizes the evidence for commonly used pharmacologic agents and presents recommendations for the sports medicine provider. Evidence Acquisition: MEDLINE searches were performed using the following keywords: sleep aids, circadian rhythm adjustment, athletes and sleep, caffeine and sports, melatonin and athletes, and sleep aids and sports. Pertinent articles were extracted and discussed. Study Design: Clinical review. Level of Evidence: Level 2. Results: There are very few available studies investigating pharmacologic sleep aids in athletes. Data from studies involving shift workers and airline personnel are more abundant and were used to formulate recommendations and conclusions. Conclusion: Melatonin, caffeine, and nonbenzodiazepine sleep aids have a role in facilitating sleep schedule changes in athletes and maximizing sports performance through sleep enhancement.